2020
DOI: 10.1155/2020/4209812
|View full text |Cite
|
Sign up to set email alerts
|

Methods of 10-Meter Walk Test and Repercussions for Reliability Obtained in Typically Developing Children

Abstract: Introduction. Research and clinical settings use the 10-meter walk test (10MWT) to measure locomotor capacity with considerable methodological diversity. Comparison between healthy and disabled children is frequent; however, the reproducibility of 10MWT using different methods is unknown. Objectives. This study analysed intrasubject, test-retest reliability, and agreement of four methods of 10MWT, exploring the influence of pace, acceleration-deceleration phases, and anthropometric measurements when calculatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…significant difference was found between the values of 6 minute walk test and the sex of the children of age group 6-12 years of which supports the result of the present study [31]. Another study also declared that there was no significant difference between the normative values obtained for male and female healthy children performing 10 meter walk test [32]. This showed that the result of the present study was in line with that of the available literature.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…significant difference was found between the values of 6 minute walk test and the sex of the children of age group 6-12 years of which supports the result of the present study [31]. Another study also declared that there was no significant difference between the normative values obtained for male and female healthy children performing 10 meter walk test [32]. This showed that the result of the present study was in line with that of the available literature.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Therefore, in this study, the Obstacles Test and Curb Test were performed with instructions to proceed at a fast speed. Implementing walking at fast speeds, as used in this study, is consistent with established timed walking tests (10 MWT, MTUG, and Timed Up and Down Stairs), which are more appropriate when performed at a fast speed [11,[30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 89%
“… Children with ambulatory CP 4 - 16 years Concurrent validity Excellent test-retest reliabilityICC=0.94 McDowell et al [ 28 ], Martakis et al [ 29 ] 10-Meter Walk Test Measure locomotor capacity in clinical and research settings. Children and adolescents with neurological dysfunction 2 - 12 years High validity in the neurological diseases Good reliability0:70 < ICC > 0:89 de Baptista et al [ 30 ] 30-s chair rise The 30-Second Chair Test is administered using a chair without arms, with height of 43.2 cm. The chair, with rubber tips on the legs, is placed against a wall to prevent it from moving.…”
Section: Resultsmentioning
confidence: 99%